2005
DOI: 10.1152/ajpgi.00360.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial transport of bile salts across MDCK cells expressing both rat Na+-taurocholate cotransporting polypeptide and rat bile salt export pump

Abstract: transport of bile salts across MDCK cells expressing both rat Na ϩ -taurocholate cotransporting polypeptide and rat bile salt export pump.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…Furthermore, transport in a vesicular system can be measured as uptake. for all conjugated bile salts tested [223]. A similar study with human NTCP and BSEP expressed in LLC-PK1 cells identified again cholate, chenodeoxycholate and ursodeoxycholate as BSEP substrates together with all conjugated bile salts tested [221].…”
Section: Transport Propertiesmentioning
confidence: 62%
See 2 more Smart Citations
“…Furthermore, transport in a vesicular system can be measured as uptake. for all conjugated bile salts tested [223]. A similar study with human NTCP and BSEP expressed in LLC-PK1 cells identified again cholate, chenodeoxycholate and ursodeoxycholate as BSEP substrates together with all conjugated bile salts tested [221].…”
Section: Transport Propertiesmentioning
confidence: 62%
“…In contrast, BSEP expressed in SF9 cell vesicles does not transport cholate [221,240], which parallels the virtual absence of unconjugated bile acids in the bile from patients with a defect in bile acid conjugation [37]. Neither the human nor the rat orthologue of Bsep transport lithocholate [221,223]. …”
Section: Transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…NTCP's major physiological substrates include all the major glycine and taurine-conjugated bile acids (48)(49)(50)(51)(52). Depending on the structure of the bile acid and NTCP ortholog, unconjugated bile acids are moderate or weak substrates ( 50,53,54 ) and sulfated bile acids appear to be only weakly transported ( 55 ). In contrast to NTCP, members of the OATP of bile acids ( 1 ).…”
mentioning
confidence: 99%
“…These cells also failed to reduce MCMV-dependent luciferase activity upon bile acid treatment (data not shown). To further substantiate the hypothesis that the import of bile acids is a necessary prerequisite for antiviral activity, an experiment was designed based on the observation that TCDC inhibits MCMV, whereas TUDC does not, and the knowledge that both compounds compete for the same bile acid transporters (50,51). Graded TUDC concentrations counteracted the antiviral activity of TCDC in a dose-dependent manner (Fig.…”
Section: Fig 1 Conjugated Bile Acids Act Antivirally Against Mouse Cymentioning
confidence: 99%